2020
DOI: 10.1001/jamasurg.2020.3336
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sarcopenia and Body Composition With Short-term Outcomes After Liver Resection for Malignant Tumors

Abstract: IMPORTANCE Previous retrospective studies have shown that sarcopenia substantially alters the postoperative and oncological outcomes after liver resection for malignant tumors. However, the evidence is limited to small retrospective studies with heterogeneous results and the lack of standardized measurements of sarcopenia.OBJECTIVE To investigate the role of sarcopenia as a risk factor associated with 90-day morbidity after liver resection for malignant tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 51 publications
3
65
2
Order By: Relevance
“…Beradi et al [ 38 ] analyzed a cohort of 234 patients undergoing liver resection for malignant tumors (hepatocellular carcinoma 43%, CRLM 41%). The patients’ characteristics were similar to ours regarding gender (67% male), age (median 66 years), BMI 27 kg/m 2 and extent of hepatectomy (major 27%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beradi et al [ 38 ] analyzed a cohort of 234 patients undergoing liver resection for malignant tumors (hepatocellular carcinoma 43%, CRLM 41%). The patients’ characteristics were similar to ours regarding gender (67% male), age (median 66 years), BMI 27 kg/m 2 and extent of hepatectomy (major 27%).…”
Section: Discussionmentioning
confidence: 99%
“…There is no information of muscle strength in the present paper. In fact, there is only one study [ 38 ] that submits this information. Interestingly, loss of muscle mass increased the complication rate only in combination with reduced grip strength.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studied have suggested that BMI measure may be biased and could provide inaccurate estimation of body composition and fat distribution because of its inadequacy to distinguish between muscle and adipose tissue [ 8 , 27 ]. Among novel techniques regarding biometric parameters, evaluations of computed tomography or magnetic resonance scans, cut at the level of the third lumbar vertebra, are emerging as promising and accurate approaches to provide a more precise assessment of body composition [ 28 ]. These evaluations require experienced radiologists and specific software that may measure cross-sectional areas of skeletal muscles and normalize them for height to obtain the skeletal muscle index (SMI).…”
Section: Detecting Malnutrition From the Very Beginning Of Cancer Care: Who Starts Well Is Half The Battlementioning
confidence: 99%
“…These evaluations require experienced radiologists and specific software that may measure cross-sectional areas of skeletal muscles and normalize them for height to obtain the skeletal muscle index (SMI). The prognostic value of these measures is very promising [ 28 ]. Bioelectric impedance analysis (BIA) is also a novel method, often used.…”
Section: Detecting Malnutrition From the Very Beginning Of Cancer Care: Who Starts Well Is Half The Battlementioning
confidence: 99%